COVID-19 and the global pandemic caused by a new coronavirus - Benavides-Rosero, Mario Fernando (Universidad y Salud, 2020)
Introduction: COVID-19 is a new respiratory disease reported initially as an atypical pneumonia in December 2019. SARS-CoV-2, the etiological agent of this pathology, probably originated from a bat viral pathogen. The unexpected transmission and pathogenicity capacities that this coronavirus acquired turned COVID-19 into a pandemic with a wide and complex arrangement of symptoms. Objective: To analyze evolutionary, molecular, biological, immunological and epidemiological aspects of this disease. Materials and methods: A narrative review of the literature concerning these topics was conducted, which was published in Pubmed mostly from January 2020. Results: SARS-CoV-2 is a new coronavirus that uses its surface protein S to infect human cells that exhibit ACE2 receptors. This pathogen is transmitted through respiratory secretions and triggers a harmful increase in pro-inflammatory chemical mediators in vulnerable individuals, an immune reaction known as cytokine storm. This hyper-inflammatory response is the cause of the alveolar lesions behind the respiratory failure observed in severe cases of COVID-19. Conclusions: In susceptible individuals, SARS-CoV-2 triggers an acute respiratory distress syndrome that requires assisted ventilatory support and immunomodulatory therapy. New therapeutic and prevention strategies are being developed to reduce the high transmission and mortality rates associated with COVID-19.